2008
DOI: 10.1111/j.1574-6941.2008.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for specificity of cultivable bacteria associated with arbuscular mycorrhizal fungal spores

Abstract: Bacteria associated with arbuscular mycorrhizal (AM) fungal spores may play functional roles in interactions between AM fungi, plant hosts and defence against plant pathogens. To study AM fungal spore-associated bacteria (AMB) with regard to diversity, source effects (AM fungal species, plant host) and antagonistic properties, we isolated AMB from surface-decontaminated spores of Glomus intraradices and Glomus mosseae extracted from field rhizospheres of Festuca ovina and Leucanthemum vulgare. Analysis of 385 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Alternatively, the microbial wash may not have established similar non-AMF soil microbial communities among treatments and, as a result, the AMF-associated microbes present in the inocula could have been responsible for the pine growth reduction in the absence of clover. For example, specific bacterial communities are known to associate with the hyphal surface of AMF and these bacterial communities in the hyphosphere differ among AMF species (Bharadwaj et al 2008;Scheublin et al 2010). This could explain the AMF family-wise effects we observed in the absence of clover and suggests that hyphosphere bacterial communities may be a key factor affecting the growth of pine seedlings in our study; perhaps indicating additional roles by which AMF phylogeny could influence interactions among soil organisms.…”
Section: Discussionmentioning
confidence: 46%
“…Alternatively, the microbial wash may not have established similar non-AMF soil microbial communities among treatments and, as a result, the AMF-associated microbes present in the inocula could have been responsible for the pine growth reduction in the absence of clover. For example, specific bacterial communities are known to associate with the hyphal surface of AMF and these bacterial communities in the hyphosphere differ among AMF species (Bharadwaj et al 2008;Scheublin et al 2010). This could explain the AMF family-wise effects we observed in the absence of clover and suggests that hyphosphere bacterial communities may be a key factor affecting the growth of pine seedlings in our study; perhaps indicating additional roles by which AMF phylogeny could influence interactions among soil organisms.…”
Section: Discussionmentioning
confidence: 46%
“…This would be in agreement with the observations made by Toljander et al (2006) on the attachment of fluorescent pseudomonads to extraradical hyphae after establishment of AM symbiotic association. Several other authors also reported association of pseudomonads with hyphae of AMF (Bianciotto et al , 1996; Roesti et al , 2005; Bharadwaj et al , 2008; Pivato et al , 2008).…”
Section: Discussionmentioning
confidence: 90%
“…AM fungi not only associate with plant roots, but also establish close associations with bacteria in the AM fungus-mycosphere and may include spores (Xavier and Germida, 2003b;Bharadwaj et al, 2008;Cruz and Ishii, 2012) and external mycelia (Mansfeld-Giese et al, 2002). Mycorrhiza-associated bacteria seem to be thriving from AM fungal exudates (Toljander et al, 2007).…”
Section: The Mycorrhizosphere Microbiomementioning
confidence: 99%